MORPHOLOGICAL AND MORPHOMETRIC CHARACTERISTICS OF THE PANCREAS IN THE DYNAMICS OF THE DEVELOPMENT OF THE EXPERIMENTAL MODEL OF PANCREATIC NECROSIS COMPLICATED BY SEPSIS - Khamdamov, B.Z.; Musoev, T.Y.; Khaydarov, F.N.; Ganiyev, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The modern principles of treating pancreatic necrosis are ineffective or ineffective at all. As our analysis of the scientific literature has shown, this dead-end moment contributes to the preservation of the so-called "expectant" tactics in the formation of sterile pancreatic necrosis. Only the formation of peripancreatic purulent complications gives rise to the use of various modern surgical technologies, pushing conservative methods of treating pancreatic necrosis into the background. In this regard, we believe that the search for criteria for predicting the course of pancreatic necrosis, and the development of its complication in the form of sepsis, based on the pathogenetic mechanisms of its formation, can increase the effectiveness and efficiency of the complex treatment of patients with this pathology. Material and methods. To achieve the desired goal, the total array of experimental studies was divided by us into 5 series of experiments: 1-series of experiments - control (intact animals), a 2-series of experiments - animals with an experimental model of acute pancreatitis, a 3-series of experiments - animals with an experimental model of acute sterile pancreatic necrosis, 4-series of experiments - animals with an experimental model of acute infected pancreatic necrosis, 5-series of experiments - animals with an experimental model of acute infected pancreatic necrosis complicated by sepsis. Morphological studies included histological and morphometric studies. Pancreatic tissue served as material for research. Morphometric studies were carried out using a standard grid measuring the diameter of the vessels of the microvasculature of the pancreas: arterioles, venules, precapillary arterioles, postcapillary venule, and capillary. Conclusion. The task aimed at improving the results of treatment of patients with acute pancreatic necrosis complicated by sepsis is possible by studying the factors leading to the progression of the necrobiotic process. Experimental substantiation is required to develop effective ways to predict the course of this disease.